2009
DOI: 10.1007/s11250-009-9379-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the level of sugarcane molasses on growth and carcass performance of Caribbean growing pigs reared under a ground sugarcane stalks feeding system

Abstract: The influence of the level of sugarcane (SC) molasses on growth performance, carcass traits, and meat quality in Creole (CR) growing pigs fed with ground sugarcane stalks (GCS)-based diet was studied in a mixed farming system context. The aim of the study was to optimize the growth performance of CR pigs with SC-molasses as an energy source in this unconventional feeding. A total of 32 CR pigs were used from 30 to 60 kg of body weight (BW). The experimental dietary treatments consisted of four levels of inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…Similar results were obtained, which showed that adding 20% molasses to the diet does not affect ADG (Brooks, 1967) and G:F (Brooks, 1972) in growing pigs compared with the treatments containing a lower level of molasses. There was no significant effect on BW and ADG in growing pigs fed 200, 400, 600, and 800 g/d of molasses, respectively (Xandé et al, 2010). However, there were some differences in the results.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Similar results were obtained, which showed that adding 20% molasses to the diet does not affect ADG (Brooks, 1967) and G:F (Brooks, 1972) in growing pigs compared with the treatments containing a lower level of molasses. There was no significant effect on BW and ADG in growing pigs fed 200, 400, 600, and 800 g/d of molasses, respectively (Xandé et al, 2010). However, there were some differences in the results.…”
Section: Discussionmentioning
confidence: 76%
“…Studies also reported similar results, which suggests that molasses did not affect the meat quality of pigs compared with control diet (Karamitros, 1987;Xandé et al, 2010). The diet containing 20% molasses did not increase the loin eye area in weaning pigs (Brooks, 1967).…”
Section: Discussionmentioning
confidence: 79%
“…Kung & Shaver (2001) reported that CP and ash have high buffering capacity. Molasses contain up to 132 g/kg DM of ash (Xande et al, 2010), while that of whey could be up to 80 g/kg DM (Ben Salem & Fraj, 2007). Zobell et al (2004) stated that good silage has lactic acid levels ranging from 30 to140 g/kg, and those of the present study were lower than that threshold, suggesting poorly fermented silages.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising because molasses has been reported to have up to 44 g CP/kg DM (Xande et al, 2010), and in whey it ranges from 106 to 130 g/kg DM (Weinberg, 2004;Formigoni et al, 2006;Ben Salem & Fraj, 2007). In addition, whey has soluble protein, which would significantly complement the mostly insoluble CP in maize cobs.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting conclusion drawn is that molecular approaches can be especially suited to gain insight into the yeast biomass production process. In the last years, the price of molasses has increased because of their use in other industrial applications such as animal feeding or bioethanol production (Arshad et al, 2008;Kopsahelis et al 2009;Xandé et al, 2010), thus rendering the evaluation of new substrates for yeast biomass propagation a trend topic for biomass producers' research. New assayed substrates include molasses mixtures with corn steep liquor (20:80), different agricultural waste products (Vu and Kim, 2009) and other possibilities as date juice (Beiroti and Hosseini, 2007) or agricultural waste sources, also called wood molasses, that can be substrate only for yeast species capable of using xylose as a carbon source.…”
Section: Molasses: a Suitable Substratementioning
confidence: 99%